The Impacts of Economic Crisis in Mongolia : Findings from Focus Group Discussions - Reva, Anna; Heltberg, Rasmus; Sodnomtseren, Altantsetseg; Sarantuya, J. (World Bank, Washington, DC, 2017)
Mongolia was hit hard by the global economic recession, notably the fall in commodity prices. Gross Domestic Product (GDP) contracted by 1.6 percent in 2009 after growth of 8.9 percent in 2008. The country is narrowly specialized in production of a few primary goods with minerals comprising 70 percent of total exports. Since mid-2008, the prices of main export goods, including copper, zinc, crude petroleum, combed goat-down and cashmere dropped by close to or more than 50 percent, though prices of coal and gold held strong. Furthermore, construction activity fell sharply in 2009 as both the public and private sectors reduced investments and bank loans became less accessible. The research was conducted in urban and rural areas of Mongolia and involved interviews and focus group discussions with about 500 people total (over the four rounds of data collection) belonging to groups identified as particularly exposed to the impacts of the crisis. The primary impacts of the crisis were observed through: 1) labor market effects (e.g. reduced salaries, increased discrimination in the labor market, intensified competition for jobs and a reduction in profitability of small businesses of the poor), 2) price shocks, and 3) social changes (e.g. increase in crime and alcohol abuse). These impacts were particularly significant for the poor.